온실가스 저감정책에 대한 에너지 다소비 제조업의 경쟁력 분석: 가격설정력 모형을 이용하여 - 한민정; Min Jeong Han; 김영덕; Young Duk Kim (자원·환경경제연구, 2011)
온실가스 저감정책이 시행되면 에너지 다소비 제조업은 비용 상승으로 인해 많은 영향을 받을 것이다. 그러나 가격설정력이 있는 산업이라면, 비용 상승을 제품 가격의 상승을 통해 소비자에게 전가시킬 것이므로 온실가스 저감정책으로 인한 피해가 적을 것이다. 따라서 본 연구는 에너지 다소비 제조업의 가격설정력을 분석함으로써, 각 산업이 온실가스 저감정책에 얼마나 취약한지 살펴보았다. 본 연구에서 사용한 가격설정력 모형은 오차수정모형을 통하여 분석하였으며, 수입재의 가격과 인건비를 주요한 설명변수로 사용하였다. 수입재의 가격에 반응을 한다면 경쟁자의 가격에 따라 가격을 설정하는 가격 순응자로 볼 수 있으며, 이러한 산업은 온실가스 저감정책에 취약할 것이다. 반면에, 국내 비용을 의미하는 인건비에 영향을 받는다면, 가격설정력이 있다고 볼 수 있으며, 온실가스 저감정책에 덜 취약할 것이다. 또한, 에너지 가격의 변동은 우리나라 뿐만 아니라 해외에도 영향을 미치므로 수입재의 가격에 반영이 되어 있을 것이다. 따라서 수입재의 가격의 순영향을 보기 위해 에너지 가격을 통제변수로 사용하였다. 추정 결과, 석유제품, 화학제품, 비금속 광물제품, 섬유제품, 자동차 제조업은 가격설정력이 있는 것으로 분석되었으므로, 이들 산업은 온실가스 저감정책에 대해 경쟁력을 가지고 있다고 볼 수 있다. When greenhouse gas mitigation policies are implemented, energy intensive manufacturing industries are influenced much due to an increase in cost. However, industries that have price setting power are damaged less by the policies. Therefore, this paper analyzes vulnerability of energy intensive manufacturing industries to the policies by measuring price setting power of the industries. We analyzed price setting power model through ECM, employing the import prices and wages as independent variables. The industries that their prices react to import prices are price takers, which their prices are determined by rival`s ones. On the other hand, the industry that their prices react to wages that mean domestic cost are price setters, and they will be less vulnerable to the policies. In addition, fluctuation of energy prices would be reflected in import prices because it influences other countries than my one. Thus, we employed energy prices as control variable to measure the net effects of import prices. As empirical results, petroleum products, chemical products, non-metallic mineral products, textiles, and motor vehicles sector have price setting power, so the industries have competitiveness on greenhouse gas mitigation policies.